PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN ALAT PERAGA TERHADAP HASIL BELAJAR SISWA PADA MATERI FLUIDA STATIS - Umboh, Sixtus Iwan; Silangen, Patricia Mardiana; diantini, asri (Universitas Negeri Manado, 2020)
The purpose of this study was to determine the effect of teaching aids PBL learning model on student learning outcomes Static Fluid material class XI Science. Researchers used two classes namely, the experimental class numbered 24 students and the control class numbered 24 students. Both classes were given tests so that researchers could know the initial abilities of students, then each treatment was given. The experimental class uses the PBL model assisted with teaching aids, the control class uses the conventional model. After being tested for the second class posttest, it was obtained tcount> t table = 9.077> 2.01174. So, through this study, researchers can conclude the learning outcomes of the Experimental class using the Problem Based Learning model assisted with props larger than the Control class using the Conventional learning model.